DETERMINAN MINAT MENGIKUTI MBKM FEB IIB DARMAJAYA: PERAN MOTIVASI SEBAGAI MODERASI - Putra, Dedi; Mustika, Dian (CENDEKIA: Jurnal Ilmu Pengetahuan, 2025)
College policies in implementing the MBKM program and positive perceptions of student’s interest in participating in the MBKM program is quite large. Motivation given to someone towards a program plays an important role in influencing how students' expectations and readiness in interest can significantly increase student participation in the program. This study aims to examine the implementation of MBKM and Student Perceptions of Interest in Participating in MBKM with Motivation as a moderating variable. 110 active undergraduate students of the Faculty of Economics and Business at Darmajaya Informatics and Business Institute who have / are taking at least 2 years / 4 semesters were used as participants in this study. Data analysis using SEM-PLS processed with Warp-PLS 8.0. The results of the analysis in the study indicate that MBKM Implementation and Student Perceptions have an affect of student’s interest in participating in the MBKM program, and Motivation is able to improve the relationship between Implementation and Perception of student’s interest in participating in the MBKM program. These findings contribute to the need to consider Higher Education Policies in investigating and developing student’s interest in participating in the MBKM program. ABSTRAKKebijakan Perguruan tinggi dalam pengimplementasi Program MBKM dan Persepsi positif tentang MBKM sangat mempengaruhi minat mahasiswa dalam mengikuti MBKM. Motivasi yang diberikan kepada seseorang terhadap suatu program sangat berperan penting dalam mempengaruhi bagaimana harapan serta kesiapan mahasiswa dalam minat dapat secara signifikan meningkatkan partisipasi mahasiswa dalam program tersebut. Penelitian ini bertujuan untuk menguji implementasi MBKM dan Persepsi Mahasiswa terhadap Minat Mengikuti MBKM dengan Motivasi sebagai variabel moderasi. 110 orang Mahasiswa Aktif Strata 1 (S1) Fakultas Ekonomi dan Bisnis di Institut Informatika dan Bisnis Darmajaya yang telah/sedang menempuh minimal 2 Tahun/4 Semester digunakan sebagai partisipan dalam penelitian ini. Analisis data menggunakan SEM-PLS yang diolah dengan Warp-PLS 8.0. Hasil dari analisis pada penelitian mengindikasikan bahwa Implementasi MBKM dan Persepsi Mahasiswa berpengaruh terhadap Minat Mengikuti MBKM, dan Motivasi mampu meningkatkan hubungan Implementasi dan Persepsi terhadap Minat mahasiswa Mengikuti MBKM. Temuan ini berkontribusi pada perlunya mempertimbangkan Kebijakan Perguruan Tinggi dalam menyelidik dan mengembangkan minat mahasiswa untuk mengikuti MBKM.